PENGGUNAAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATERI SISTEM PERSAMAAN LINEAR DAN KUADRAT: PENELITIAN TERHADAP SISWA KELAS X AKUNTANSI 2 SMK NEGERI 1 TASIKMALAYA - Nurkomala, Nani (LPPM Universitas Bina Bangsa, 2022)
A contextual approach is thought to be able to make students active in the learning process. Therefore, the researcher intends to carry out research using a contextual approach to the material on systems of linear and quadratic equations in class The aim of this research is to determine whether or not the contextual learning model can improve learning outcomes for students in class X Accounting 2 at SMK Negeri 1 Tasikmalaya for the 2022/2023 academic year. Classroom action research using descriptive research methods. The research subjects were 38 people in class X Accounting 2 of SMK Negeri 1 Tasikmalaya City. The research was carried out with 3 learning cycles. Data is collected by carrying out tests every cycle, daily tests, observations, and questionnaires. Based on the analysis of the collected data, it was concluded that using a contextual approach to the material on systems of linear and quadratic equations, the average aspect of understanding the problem was 93.65%, the aspect of planning the solution was 67.25%, the aspect of carrying out the solution was 87.69% and the aspect of checking the results 63.94 %. Learning with a contextual approach can improve students' abilities in solving problems in systems of linear and quadratic equations. This can be seen from the increase in average mastery of each cycle and daily test. From cycle I to cycle II it increased by 14.63% and from cycle II to cycle III it increased by 12.67%